P094: Evaluation of the National Early Warning Score (NEWS) to guide the orientation of patients with sepsis in the emergency department. (May 2019) - Negreanu, D.; Hegg, S.; Malo, C.; Yaccarini, O.; Émond, M.
Abstract : Introduction : The Canadian Triage and Acuity Scale (CTAS) identifies the level of urgency when patients arrive to the Emergency department (ED). Sepsis is challenging to recognize and is associated with significant mortality (30 to 50%). The integration of the COP criteria allows for earlier detection and management of sepsis.The CTAS's validity and reliability are debated. The NEWS score has been suggested to allow a timely recognition of sepsis.Objectives:To describe patient orientation at ED triage with the NEWS vs. the CTAS and COP criteria and to identify the NEWS's ability to detect patients who will require admission to critical care.Methods : Design: A retrospective cohort study of ED 225 patients (January-November 2018) is was constituted.Participants : Patients were included if they were aged ≥18, consulting to the ED, presented one of the 32 diagnoses included in the CMI-10.Measurements : Retained variables are sex, age, CTAS score and level of care. The NEWS score was calculated from triage vital signs. Main outcome was Patient orientation after ED triage using CTAS vs the NEWS score. Descriptive statistics to determine patient orientation based on the NEWS and CTAS were performed. Fisher tests (α = 0.05) were used to assess a possible association between both triage scales and identify the NEWS's ability to detect patients who will require admission to critical care during. Sample size was calculated in order to detect a 15% difference between actual orientation and theoretical orientation based on the NEWS.Results : The retained cohort (45% men) were aged 66 ± 21 years. 67% were admitted, 14% of which to a critical care unit. Average length of hospital stay was 6.3 ± 7.8 days. Primary objective: patient orientation after triage using CTAS vs the NEWS was: 29% vs. 18% for high risk patients; 2% vs. 67% for low risk patients (p < 0.0001), respectively. Secondary objective: Among patients with stable NEWS score, 53% were admitted to hospital among patients with medium NEWS score, 9% of patients were admitted to the critical care (p = 0.0003)Conclusion : Patient orientation after ED triage using CTAS vs the NEWS is significantly different. The NEWS alone does not seem to be able to detect patients who will require admission to critical care. Future studies exploring an aggregate scoring system combining the NEWS and CTAS could be performed to determine if sepsis recognition and patient orientation can be improved